OPTICAL DEVICE AND OPTICAL COMMUNICATION APPARATUS - MAKINO SHUNTARO; YOSHIDA HIROHIKO; MITAMURA NOBUAKI; KUBOTA YOSHINOBU (2022)
To provide an optical device and an optical communication apparatus that can be miniaturized and driven at a low voltage by improving modulation efficiency.SOLUTION: An optical device includes: a silicon substrate; a waveguide laminated on the silicon substrate and formed of a thin film of a perovskite-type oxide having a greater electrooptical effect than lithium niobate; and a clad layer that covers the waveguide. The optical device further includes: a ground electrode of a ground potential and a signal electrode that is arranged at a position facing the ground electrode and applies a drive voltage to the waveguide.SELECTED DRAWING: Figure 4 【課題】変調効率の向上を図ることで小型化及び低駆動電圧化を図る光デバイス及び光通信装置を提供することを目的とする。【解決手段】光デバイスは、シリコン基板と、前記シリコン基板上に積層された、ニオブ酸リチウムに比較して電気光学効果が大きいペロブスカイト型酸化物の薄膜で形成された導波路と、前記導波路を被覆するクラッド層と、を有する。更に、光デバイスは、接地電位の接地電極と、前記接地電極と対向する位置に配置され、前記導波路に駆動電圧を印加する信号電極と、を有する。【選択図】図４